Pengaruh Kualitas Produk, Harga Dan Customer Review Terhadap Keputusan Pembelian Kosmetik MakeOver - Pakpahan, Widya Putri Rossalina; Wijaya, Trisnadi (MDP Student Conference, 2025)
The purpose of this study is to analyze the influence of product quality, price and customer reviews on the decision to purchase MakeOver cosmetics partially and simultaneously. This study uses a questionnaire distribution method with a Likert scale, with a total of 230 respondents. The type of research used is a quantitative method. The sampling technique was taken using the purposive sampling technique and the Roscoe formula method. The data processing of this study uses the help of SPSS 26 software. The results of this study show that the partial test (t-test) of product quality variables (X1), price (X2), and customer review (X3) have a positive and significant effect on purchase decisions. The Simultaneous Test (F-test) proved that the variables of product quality (X1), price (X2), and customer review (X3) had an effect on the dependent variable, namely the purchase decision (Y).